PREVALENSI DAN INTENSITAS EKTOPARASIT PADA IKAN NILA (Oreocromis niloticus) YANG DIBERI PAKAN BUNGKIL KELAPA HASIL FERMENTASI DALAM WADAH TERKONTROL - Harlina Harlina; Sitti Hadijah; Kamaruddin Kamaruddin; Nurhidayah Nurhidayah; Nurwahyudin Nurwahyudin (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2019)
An ectoparasitic infection is one of the causes of losses for the farmers of red tilapia (Oreochromis niloticus). This study was aimed to determine the types of parasites, the level of attack includes the prevalence, intensity and dominance of ectoparasites in red tilapia by adding fermented copra meal to the feed. The research was carried out at the Maros Fish Farming Center, South Sulawesi, while observing parasites in fish were carried out at the BRBAPPP Fish Pathology and Health Laboratory, Maros. The treatments were tested by addition of fermented copra meal as follows: (A) 0% control; (B) 15%; (C) 30% and (D) 45%. The experimental feed was applied to the fish once a day by satiation. The parameters observed were 1) identification of parasites; 2) prevalence rate; 3) attack intensity; 4) dominance and 5) water quality. A total of 30 tilapia from containers were taken to observe the fish organs included, ectoparasites were observed using a smear method on the target organ (gills, scales and fins and eyes), then examined microscopically. The ectoparasites were identified based on Kabata (1985), Grabda (1981) and Moller and Anders (1986). The result found two types of parasites namely Argulus sp. and Epistylis sp. The result of the prevalence of Argulus sp. of treatments A, B, and D were obtained (3.33%) and intensity (1 ind/fish) except that Treatment C was obtained prevalence and intensity (0%). While the highest prevalence rate of Vorticella sp. in A (Control) was 20% (frequent infections) while other treatments were still relatively low at 3.33% - 13.3% (sometimes infections) with intensity of attacks 0-1 ind / fish (low infection rate). The dominance value in all treatments ranged from 0.1 to 0.85%. The range of water quality of fish container were temperature 26.3-29.2 °C, pH 7.5-7.8, DO 5.8-6.4 ppm and ammonia 0.02-0.26 ppm. The value was within good range for Red Tilapia.